Subjective Perceptions of Financing Constraints: How Well Do They Reflect Credit Market Conditions? - Bouton, Lawrence; Tiongson, Erwin R. (2012)
Many cross-country enterprise surveys have recently become widely available. They are the basis of rankings of dimensions of the business environment in emerging markets and developing economies. Although the literature is concerned about "perception bias", there has been little effort at analyzing whether subjective appraisals of credit market constraints correspond to objectively measurable indicators. This note assesses a predominantly used subjective measure of "access to finance" and relates it to indicators of financial development and credit availability and costs. It finds a significant relationship between subjective and objective indexes of financing constraint but the relationship varies substantially across indicators.